2011
DOI: 10.1103/physreve.84.051908
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the edge of chaos: Amplification and temporal integration by recurrent networks in the chaotic regime

Abstract: Randomly connected networks of neurons exhibit a transition from fixed-point to chaotic activity as the variance of their synaptic connection strengths is increased. In this study, we analytically evaluate how well a small external input can be reconstructed from a sparse linear readout of network activity. At the transition point, known as the edge of chaos, networks display a number of desirable features, including large gains and integration times. Away from this edge, in the nonchaotic regime that has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
134
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(146 citation statements)
references
References 19 publications
(32 reference statements)
5
134
1
1
Order By: Relevance
“…We can easily see thatq = 0 is a solution of Eq. (A4) [5]. Hence, ifq = 0, the average · L0 ≡ · L |q =0 is an average over Gaussian h of mean h t L0 = 0 and covariance h t h s L0 = q ts , which simplifies the saddle-point equation of Eq.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…We can easily see thatq = 0 is a solution of Eq. (A4) [5]. Hence, ifq = 0, the average · L0 ≡ · L |q =0 is an average over Gaussian h of mean h t L0 = 0 and covariance h t h s L0 = q ts , which simplifies the saddle-point equation of Eq.…”
Section: Discussionmentioning
confidence: 98%
“…The binomial distribution in Eq. (5) suggests that the state overlap for each neuron is approximately independent, occurring with probability (1 + ϕ(q ′ ))/2 (see Appendix A for a support). A similar expression is obtained for random Boolean networks by replacing ϕ(q) with ϕ BN (q) ≡ δ q,1 , simply reflecting completely random nature of state transitions.…”
Section: Mean-field Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The second type of chaotic firing pattern 17 is the synchronous chaos. Synchronous chaos has been demonstrated in networks of 18 both biophysical and non-biophysical neurons [3,13,15,17,[22][23][24], where neurons display 19 synchronous chaotic firing-rate fluctuations. The latter cases, the chaotic behavior is a 20 result of network connectivity, since isolated neurons do not display chaotic dynamics or 21 burst firing.…”
mentioning
confidence: 99%
“…More recently, a totally different mechanism showed that asynchronous 22 chaos, where neurons exhibit asynchronous chaotic firing-rate fluctuations, emerge 23 generically from balanced networks with multiple time scales synaptic dynamics [20]. 24 Different modeling approaches have been used to uncover important conditions for 25 observing these types of chaotic behavior (in particular, synchronous and asynchronous 26 chaos) in neural networks, such as the synaptic strength [25][26][27] in a network, 27 heterogeneity of the numbers of synapses and their synaptic strengths [28,29], and lately 28 the balance of excitation and inhibition [21] . The results obtained by Sompolinsky et 29 al.…”
mentioning
confidence: 99%